A conversation rewound: Queer and racialized temporalities in Hamilton. Issue 2 (1st June 2018) - Inayatulla, Shereen; Silva, Andie
The authors of this article, two educators and immigrants situated in the United States, consider the exigencies of listening to Hamilton: An American Musical. Shaped as dialogue, this article follows a previous piece where the authors processed their experience seeing Hamilton performed live. The current conversation shifts to the act of listening; it examines the ways in which the soundtrack embeds the audience into Lin-Manuel Miranda's narrative, reinscribing the racialized immigrant body onto both Alexander Hamilton's story, and Hamilton, the musical. Additionally, this article asks how the fictional Hamilton's message to rise up and take a shot grants audience members a sense of agency and compels them to become present/future protagonists of a political story that seeks to write them off.